Exploring diagnostic frontiers in oral squamous cell carcinoma: A comprehensive review from immunohistochemistry to genomic profiling - Hema Suryawanshi; Alka Hande; Kaladhar Reddy Aileni; Manisha Sahu; Santosh R. Patil; Mohmed Isaqali Karobari (Oral Oncology Reports)
Oral Squamous Cell Carcinoma (OSCC) management requires precise and effective strategies to assess the surgical margins. Integrating diagnostic markers into this evaluation presents a promising avenue for improving treatment approaches and improving patient outcomes. This review emphasizes the critical role of diagnostic markers in risk stratification, allowing for tailored treatment strategies that significantly improve the probability of successful surgical outcomes. However, challenges such as standardization, variability in expression, and need for validation in diverse cohorts of patients have hindered the widespread adoption of diagnostic markers in routine clinical practice. Future research priorities include rigorous validation of diagnostic markers, development of standardized assessment protocols, and exploration of novel markers to overcome the existing limitations. A multidisciplinary approach involving collaboration between surgeons, pathologists, and researchers is crucial for advancing the field and optimizing OSCC management. Although diagnostic markers hold promise for revolutionizing surgical margin assessment in OSCC, addressing challenges, validating efficacy, and collaborative efforts are imperative for their successful translation into routine clinical practice.